Increasing the sensitivity of MRI for the detection of multiple sclerosis lesions by long axial coverage of the spinal cord: a prospective study in 119 patients - Breckwoldt, Michael O.; Hähnel, Stefan; Wildemann, Brigitte; Diem, Ricarda; Platten, Michael; Wick, Wolfgang; Heiland, Sabine; Bendszus, Martin (Journal of neurology, 2017)
Diagnostic imaging criteria of multiple sclerosis (MS) include the spatial and temporal dissemination of cerebral and/or spinal cord lesions. Magnetic resonance imaging (MRI) is the method of choice for initial diagnosis and follow-up disease monitoring. Current guidelines for spinal MRI recommend sagittal imaging of the spinal cord and lesion confirmation on axial planes if lesions are detected. Sagittal imaging is, however, hampered by technical (e.g. partial volume effects, motion artifacts) and anatomical (e.g. scoliosis) limitations. We hypothesized that long coverage of the spinal cord by axial image acquisition has superior diagnostic performance compared to sagittal imaging and can identify otherwise undetected lesions. Our prospective clinical study included 119 MS patients. Axial MRI revealed ~2.5-fold more lesions than the sagittal angulation (axial lesion load: 4.0 ± 2.4 vs. 1.6 ± 1.2 lesions on sagittal planes, p < 0.001). Importantly, 20 patients (17%) with normal sagittal MRI scans had unequivocal lesions only visible on axial planes (mean lesion number on axial planes in these patients: 2.0 ± 1.3). Moreover, 45 patients (38%) showed a discrepancy of ≥3 lesions that were found additionally on axial scans (mean difference 4.4 ± 1.7). Additionally identified lesions were on average smaller in size and located more laterally within the spinal cord. No lesion on sagittal images was missed on the axial angulation. Our study demonstrates that imaging of small axial segments for lesion confirmation is insufficient in spinal imaging. We recommend implementing a long coverage axial MRI sequence for spinal imaging of MS patients.
Published online: 1 December 2016
Gesehen am 25.06.2018